DEVELOPMENT OF MEDICAL AND HEALTH TOURISM IN THE RESORT REGIONS OF THE LEADING COUNTRIES OF WESTERN EUROPE (Development Service Industry Management, 2024)
The main types of health tourism are considered, the main functional components of resorts are defined: wellness tourism establishments and special institutions and facilities for medical use. They, in turn, are further divided into subspecies. It was found that the health tourism market changes every year due to new classifications and newly developed tourist services for tourists. While retaining its foundational principles, medical tourism continues to evolve, introducing diverse specialized programs for rehabilitation and flexible recovery plans. Based on the regional analysis, Germany has been found to dominate the market for a long time. The development of medical and health tourism in Europe has led to the compilation of a 2022 ranking of the most visited spa centers, with several located in Western Europe. A feature of health tourism services in the countries of Western Europe is the infrastructure, which is also supported and updated thanks to profits from other sectors of the countries' tourism market. On the territory of the countries of Western Europe, there are world-famous objects of medical and health tourism, which is one of the reasons for the demand of tourists in these countries. Also, this region provides a variety of professional services and tourist products, which are in wide demand in the global market of medical and health tourism. The statistical indicators of the health care market are determined and the statistical data of tourist flows to the countries of Western Europe are given, as well as the rating of health care facilities of Western countries, which are leaders in the European and World rankings, was created. According to the data, statistics of the best medical and health facilities in Western Europe and the World were created, where France takes the first place, the institution – this rating includes other countries of Western Europe, among them Germany, Switzerland, Belgium, Austria, the Netherlands and Luxembourg. According to The Global Wellness Economy: Country Rankings of 2023, the top of the largest markets in Europe was created – the first place is occupied by Germany – 223.9 billion dollars, the second place is Great Britain –158.4 billion dollars, the third place – France – 133.1 billion dollars. It has been determined that there are about 900 spas in Germany, including mineral, mud, climatic, marine and hydrotherapy resorts, as well as 700 ski resorts. The French market consists of 625 spas and 249 ski resorts. Switzerland has more than 300 ski resorts, including Davos and St. Moritz. In Austria, there are famous balneological resorts of Badgastein, where radon sources are used. Austria has more than 400 ski resorts, some of which are world-famous. More than 300 ski resorts are located in Switzerland.
Keywords: medical and health tourism; resort; medical and health facilities; educational and health tour; countries of Western Europe